Papillary Renal Cell Carcinoma: Demographics, Survival Analysis, Racial Disparities, and Genomic Landscape (Journal of Kidney Cancer, 2023)
Papillary renal cell carcinoma (PRCC) is the second most common histological subtype of renal cell cancer. This research aims to present a large database study highlighting the demographic, clinical, and pathological factors, racial disparities, prognosis, and survival of PRCC. The clinical and demographic data were extracted from the Surveillance, Epidemiology, and End Results (SEER) database, and molecular data was cured from the Catalogue Of Somatic Mutations in Cancer (COSMIC) database. PRCC had a median age of diagnosis at 64 years, with a higher incidence in men (77%), and Whites (68%). 70.3% of cases were Grades I–IV (13, 53, 31, and 3%, respectively). In patients with known data, 85% were localized to the kidney, and 84% of cases were 7 cm in size. No metastasis occurred in 97% of the known data. The most common treatment offered was surgical resection (9%). The 5-year overall survival was 79%, with patients undergoing surgery having a 90.6% 5-year survival. Multivariable analysis revealed age > 60 years, Black race, poor histologic differentiation, distant metastases, and tumor size > 10 cm as independent risk factors for mortality. The most common mutations identified from the COSMIC database were MET, KMT2D, KMT2C, ARID1A, and SPEN. PRCC affects male individuals in the sixth decade of life. Increased age, Black race, distant metastases, and tumors > 10 cm are associated with a worse prognosis. Surgical resection offers a favorable survival outcome. Next-generation sequencing (NGS) could identify potentially targetable alterations and future personalized therapeutic approaches.